Various Bee Pheromones Binding Affinity, Exclusive Chemosensillar Localization, and Key Amino Acid Sites Reveal the Distinctive Characteristics of Odorant-Binding Protein 11 in the Eastern Honey Bee, Apis cerana - Song, Xin-Mi; Zhang, Lin-Ya; Fu, Xiao-Bin; Wu, Fan; Tan, Jing; Li, Hong-Liang (Frontiers in Physiology, 2018)
Odorant-binding proteins (OBPs) are the critical elements responsible for binding and transporting odors and pheromones in the sensitive olfactory system in insects. Honey bees are representative social insects that have complex odorants and pheromone communication systems relative to solitary insects. Here, we first cloned and characterized OBP11 (AcerOBP11), from the worker bees antennae of Eastern honey bee, Apis cerana. Based on sequence and phylogenetic analysis, most sequences homologous to AcerOBP11 belong to the typical OBPs family. The transcriptional expression profiles showed that AcerOBP11 was expressed throughout the developmental stages and highly specifically expressed in adult antennae. Using immunofluorescence localization, AcerOBP11 in worker bees’ antennae was only localized in the sensilla basiconica (SB) near the fringe of each segment. Fluorescence ligand-binding assay showed that AcerOBP11 protein had strong binding affinity with the tested various bee pheromones components, including the main queen mandibular pheromones (QMPs), methyl p-hydroxybenzoate (HOB) and (E)-9-oxo-2-decanoic acid (9-ODA), alarm pheromone (n-hexanol), and worker pheromone components. AcerOBP11 also had strong binding affinity to plant volatiles, such as 4-Allylveratrole. Based on the docking and site-directed mutagenesis, two key amino acid residues (Ile97 and Ile140) were involved in the binding of AcerOBP11 to various bee pheromones. Taken together, we identified that AcerOBP11 was localized in a single type of antennal chemosensilla and had complex ligand-binding properties, which confer the dual-role with the primary characteristics of sensing various bee pheromones and secondary characteristics of sensing general odorants. This study not only prompts the theoretical basis of OBPs-mediated bee pheromones recognition of honey bee, but also extends the understanding of differences in pheromone communication between social and solitary insects.